Проблемы вещно-правовой защиты права собственности - Timofeyeva, Mariya (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The aim of the study is to evaluate the property rights protection system in the civil law system of the Russian Federation. The author present the law instruments that owner and possessor are entitled to by focusing on the law regulation and judicature.
Selected problems of the protection of property rights in the Russian Federation
Keywords: protection of property rights; owner; possessor; civil law